2015
DOI: 10.1002/jcp.24905
|View full text |Cite
|
Sign up to set email alerts
|

TNF-related weak inducer of apoptosis (TWEAK) regulates junctional proteins in tubular epithelial cells via canonical NF-κB pathway and ERK activation

Abstract: The tubular epithelium may be intrinsically involved in promoting kidney injury by junctional instability, epithelial-mesenchymal transition (EMT) and extracellular matrix remodelling. In this work, we investigated whether the pleiotropic and proinflammatory cytokine tumor necrosis factor-like weak inducer of apoptosis (TWEAK), could be able to disturb junctional protein expression and to induce EMT of tubular cells. In cultured murine proximal tubular cells TWEAK induced phenotypic changes that were accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 67 publications
(87 reference statements)
1
31
0
Order By: Relevance
“…MAPK/ERK signaling is an important pathway that affects cell proliferation, and can be activated by growth factors such as TGF-β1 [26], [27], [28]. Because our data showed that GTP induced the expression of TGF-β1, we therefore examined the effect of GTP on ERK signaling pathway by Western blotting and immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK/ERK signaling is an important pathway that affects cell proliferation, and can be activated by growth factors such as TGF-β1 [26], [27], [28]. Because our data showed that GTP induced the expression of TGF-β1, we therefore examined the effect of GTP on ERK signaling pathway by Western blotting and immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that TWEAK regulates junctional proteins in cells via canonical NF-κB pathway and ERK activation (30). Our results showed that the TWEAK-induced Ro52 expression in keratinocytes can be suppressed by NF-κB or PI3K/Akt inhibitor but enhanced by MAPK/ERK inhibitor, suggesting that the NF-κB and PI3K pathways participate in the TWEAK regulation of Ro52.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 TWEAK promotes partial EMT in renal tubular cells. 58 TWEAK-induced EMT was TGF-β1-and EGFR-independent, 58 in contrast to other profibrotic factors, such as angiotensin II. The EMT process triggered by TWEAK involves the activation of the classic NF-κB pathway and the MAPK ERK1/ 2 and the integration of both signaling pathways to downmodulate the expression of the vitamin D receptor.…”
Section: Profibrotic Actions Of Tweak In Kidney Cellsmentioning
confidence: 98%
“…Pharmacologic modulation of NF-κB and ERK activation, as well as restoration of vitamin D-receptor levels, restricted TWEAK-mediated EMT. 58 TWEAK-induced TGF-β1 up-regulation via Rasdependent protein kinase G type 1 (PKG-1) downregulation resulted in extracellular matrix production by cultured mesangial cells and in the whole kidney in vivo. 59 TWEAK also induces H/N-Ras/ERK-mediated proliferation and NF-κB-mediated release of inflammatory mediators in cultured renal fibroblasts.…”
Section: Profibrotic Actions Of Tweak In Kidney Cellsmentioning
confidence: 99%